Pengaruh Konsep Diri, Gaya Hidup, dan Perilaku Konsumtif Terhadap Literasi keuangan Mahasiswa Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Bengkulu - Erwani Yusuf; Novita Wahyu Ningsih (Universitas Dehasen Bengkulu, 2022)
This study aims to examine and determine whether there is an influence between financial literacy on self-concept, lifestyle and consumptive behavior of Economic Education Students, Faculty of Teacher Training and Education, University of Muhammadiyah Bengkulu. This researcher is a quantitative research with data collection techniques using a questionnaire. The sample is 50 students of economic education. The sampling technique used is a systematic sampling technique by taking the student principal number system with odd sequence numbers. Primary data processing using statistical analysis techniques package for social science (SPSS 26) with multiple regression analysis method. The results of this study indicate that financial literacy on self-concept has a significant value of 0.0 < 5% = (0.05) with a tcount of 430.1. Financial literacy on lifestyle has a tcount value of 2,565. Financial literacy on consumptive behavior has a tcount of 1.662. And after being tested together, it can be concluded that the most partial is the self-concept that the tcount value is 3.361 and the ANOVA fcount test results are 6.444, the r2 value is 29.6%, the rest is influenced by other factors not examined in this study.